1998
DOI: 10.1046/j.1365-2222.1998.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among urinary eosinophil protein X, leukotriene E4, and 11‐dehydrothromboxane B2 in patients with spontaneous asthmatic attack

Abstract: Various kinds of cells and their mediators are thought to be involved in the pathogenesis of bronchial asthma. However, changes in each mediator or relationship among mediators during an asthmatic attack have not been well documented. In this study, to clarify whether eosinophil protein X (EPX) is a marker which is distinct from leukotriene E4 (LTE4), or 11-dehydrothromboxane B2 (11DTXB2), we measured the urinary excretion of EPX, LTE4, and 11DTXB2 in 14 asthmatics who were admitted to the hospital with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
17
3
Order By: Relevance
“…2 It was also found that human basophils produce high levels of IL-4 in the lung after segmental allergen challenge. 3 Oosaki et al 4 reported that in patients with spontaneous asthma attacks, urinary excretions of eosinophil protein X, leukotriene E4, and 11-dehydrothromboxane B2 significantly increase during the attack and return to control levels in the improved phase. In addition, Nakano et al 5 showed that patients admitted to a hospital because of nonresolving asthma exacerbation had higher plasma levels of C3a, a potent proinflammatory mediator, than patients discharged immediately after the exacerbation or patients with stable asthma.…”
mentioning
confidence: 98%
“…2 It was also found that human basophils produce high levels of IL-4 in the lung after segmental allergen challenge. 3 Oosaki et al 4 reported that in patients with spontaneous asthma attacks, urinary excretions of eosinophil protein X, leukotriene E4, and 11-dehydrothromboxane B2 significantly increase during the attack and return to control levels in the improved phase. In addition, Nakano et al 5 showed that patients admitted to a hospital because of nonresolving asthma exacerbation had higher plasma levels of C3a, a potent proinflammatory mediator, than patients discharged immediately after the exacerbation or patients with stable asthma.…”
mentioning
confidence: 98%
“…6,7 Previous studies have shown that the U-LTE4 concentration is useful in demonstrating cys-LT release in vivo during allergen challenge 8,9 and acute exacerbation of asthma. 10,11 Moreover, even in clinically stable conditions, basal urinary excretion levels of LTE4 in patients with aspirin-intolerant asthma (AIA) are significantly higher than those in patients with aspirin-tolerant asthma (ATA). 12,13 The cellular source of cys-LTs is as yet unknown, but it possibly includes eosinophils and mast cells.…”
mentioning
confidence: 99%
“…The relationship between urinary LTE 4 and 11DTXB 2 in the pathogenesis of asthma has been reported by several investigators; [2][3][4][5]8,11,13,20 because of the instability of CysLTs and TXA 2 , the end-products of the cascade were determined. However, most studies have been Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, increased production of CysLTs in asthmatic patients in vivo has been observed in several studies. [1][2][3][4][5]11,12 A potent bronchoconstrictor, TXA 2 is generated from arachidonic acid by cyclooxygenase. Enhanced TXA 2 release has also been reported in asthmatic patients after allergen challenge.…”
Section: Introductionmentioning
confidence: 99%